Retracted: Methane emissions from the Marcellus Shale in southwestern Pennsylvania and northern West Virginia based on airborne measurements. Issue 8 (20th April 2017) - Ren, Xinrong; Hall, Dolly L.; Vinciguerra, Timothy; Benish, Sarah E.; Stratton, Phillip R.; Ahn, Doyeon; Hansford, Jonathan R.; Cohen, Mark D.; Sahu, Sayantan; He, Hao; Grimes, Courtney; Salawitch, Ross J.; et al.
Abstract: Natural gas production in the U.S. has increased rapidly over the past decade, along with concerns about methane (CH4 ) leakage (total fugitive emissions), and climate impacts. Quantification of CH4 emissions from oil and natural gas (O&NG) operations is important for establishing scientifically sound, cost‐effective policies for mitigating greenhouse gases. We use aircraft measurements and a mass balance approach for three flight experiments in August and September 2015 to estimate CH4 emissions from O&NG operations in the southwestern Marcellus Shale region. We estimate the mean ± 1 σ CH4 emission rate as 36.7 ± 1.9 kg CH4 s −1 (or 1.16 ± 0.06 Tg CH4 yr −1 ) with 59% coming from O&NG operations. We estimate the mean ± 1 σ CH4 leak rate from O&NG operations as 3.9 ± 0.4% with a lower limit of 1.5% and an upper limit of 6.3%. This leak rate is broadly consistent with the results from several recent top‐down studies but higher than the results from a few other observational studies as well as in the U.S. Environmental Protection Agency CH4 emission inventory. However, a substantial source of CH4 was found to contain little ethane (C2 H6 ), possibly due to coalbed CH4 emitted either directly from coalmines or from wells drilled through coalbed layers. Although recent regulations requiring capture of gas from the completion venting step of the hydraulic fracturing appear to have reduced losses, our study suggests that for a 20 year time scale, energy derived from the combustion of natural gas extracted from this region will require further controls before it can exert a net climate benefit compared to coal. Key Points: Significant methane emissions of 37 kg s −1 were observed from a 4235 km 2 area of the southwestern Marcellus Shale region We estimate a mean CH4 leak rate of 3.9% from O&NG operations in the SW Marcellus with a lower limit of 1.5% and an upper limit of 6.3% The estimated mean CH4 leak rate exceeds the 2.4% tipping point relative to coal combustion for the methane GWP over a 20 year time horizon